Kebijakan Dividen dan Manajemen Laba: Analisis Pendekatan Regresi Data Panel - S, Maulidin; Rahmazaniati, Linda (Akbis: Media Riset Akuntansi dan Bisnis, 2024)
This study aims to determine how dividend policy affects earnings management. Manufacturing companies that are listed on the Indonesia Stock Exchange are the focus of this study.The extended time of perception taken in this study was in the 2019-2021 period or 3 years of perception.Using secondary data, this study employs a quantitative approach.Purposive sampling was used to select the sample for this study, and 29 samples were taken from businesses that met the research criteria.Eviews 12 were used for panel data analysis with an alpha level of 5%.In manufacturing companies that are listed on the Indonesia Stock Exchange, it was discovered that dividend policy influences earnings management.